(untitled) (Cambridge [England], 1993)
Whether there is a future to predict is not a question many people care to think about too deeply, though the process of predicting the future has itself a history. We did not always predict from the same assumptions as we do now, or for the same reasons. Today, on the basis of empirical observation and scientific theory, accredited experts and specialists forecast the economy, the social consequences of medical innovation and even what will happen to the universe in billions of years time. In the past soothsayers, priests, oracles and comets foretold the future on the basis of religious ideology and traditional authority. In a remarkable series of thought-provoking essays the authors examine both approaches and their consequences and chart our continuing attempts to see beyond the present.
Keywords: Forecasting,Divination,Dự đoán,Thuật bói toán